Effects of Probiotic (Bacillus subtilis) on Laying Performance, Blood Biochemical Properties and Intestinal Microflora of Shaoxing Duck - Li, Wei Fen; Rajput, Imran Rashid; Xu, Xin; Li, Ya Li; Lei, Jian; Huang, Qin; Wang , Min Qi (International Journal of Poultry Science, 2011)
The study was conducted to evaluate the effects of probiotic supplementation (Bacillus subtilis) in diet on performance, blood properties and microflora of Shaoxing duck. A population of 200 laying ducks (160 days old) was divided into two groups each having five replications. The control (T0) were fed on basal diet while T1 with Bacillus subtilis 1 x 108 CFU/kg in addition to basal diet for thirty five days. The results showed that for T1 group, the egg laying rate increased (3.79%) significantly, while a decrease of about 12.60%, 23.52% and 40.14% was observed in egg triglyceride, total cholesterol and malondialdehyde, respectively. However, the blood glucose content and alkaline phosphatase activity increased by 15.13% and 53.41%, significantly. Moreover, there was a decrease of blood cholesterol, uric acid and ammonia in T1 by 28.86%, 22.39% and 62.5%, respectively. As compared to T0, T1 showed a significant increased in the amount of caecal microflora, i.e. general aerobic bacteria (18.68%) and Lactobacillus (9.92%). In conclusion, supplementation of Bacillus subtilis in diets had significant effects on some aspects of egg composition, biochemical properties of blood and few microflora of Shaoxing ducks.